2021
DOI: 10.3390/ijerph182111140
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Stress and Its Correlates among Pregnant Women during the Second Wave of COVID-19 in Poland

Abstract: Background: The ongoing COVID-19 pandemic has created numerous stressful conditions, especially for vulnerable populations such as pregnant women. Pandemic-related pregnancy stress consists of two dimensions: stress associated with feeling unprepared for birth due to the pandemic (Preparedness Stress), and stress related to fears of perinatal COVID-19 infection (Perinatal Infection Stress). The purpose of our study was to elucidate the association between various factors—sociodemographic, obstetric, pandemic-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
3
12
0
1
Order By: Relevance
“…In other studies conducted in Poland during the pandemic, a moderate and positive relationship among women was observed between perceived stress, fear of COVID-19 and fear of childbirth [ 24 ]. Ilska et al [ 26 ] noted that during the second wave of the pandemic, almost 38.5% of pregnant women reported high preparedness stress and 26% reported high perinatal infection stress. In turn, Jiang et al [ 62 ] observed that in China in February 2020 the prevalence of perceived stress in pregnancy was 89.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies conducted in Poland during the pandemic, a moderate and positive relationship among women was observed between perceived stress, fear of COVID-19 and fear of childbirth [ 24 ]. Ilska et al [ 26 ] noted that during the second wave of the pandemic, almost 38.5% of pregnant women reported high preparedness stress and 26% reported high perinatal infection stress. In turn, Jiang et al [ 62 ] observed that in China in February 2020 the prevalence of perceived stress in pregnancy was 89.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we compared the psychophysical condition of women who gave birth during different periods of the pandemic (December 2019–March 2020, May–September 2020, June–September 2021). To our knowledge, there are currently no publications assessing the psychophysical condition of women who gave birth in Poland during three different periods of the pandemic [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The level of pandemic stress in the current study is greater than the level of pandemic stress in previous studies. A study conducted by Ilska [12] on 1,119 pregnant women revealed that approximately one-third of pregnant women reported having elevated levels of both preparedness and infection stress.…”
Section: Discussionmentioning
confidence: 99%
“…This tool was developed by the researcher after reviewing the related literature. [11,12] Tool (2): The Pandemic -Related Pregnancy Stress Scale (PREPS): This tool was adapted from. [13] The Pandemic-Related Pregnancy Stress Scale (PREPS) is a novel instrument that measures prenatal stress at the time of the pandemic.…”
Section: Tool Of Data Collectionmentioning
confidence: 99%
“…However, there has lack of attention to the investigation linked to gender issues while at the same time women are recognized as the most vulnerable groups during the pandemic (Ilska, Kołodziej-Zaleska, Brandt-Salmeri, Preis, & Lobel, 2021;Kouassi et al, 2012). The United Nations identifies there are four potential risks experienced by women; a) economically, women feel the impact directly because they generally earn less; b) neglected women's health reallocation of health resources and priorities, including reproductive health services; c) women have an increased workload at home due to changes in social behavior where most activities are carried out from home, including children's school activities; d) there is an increase in gender-based violence increasing exponentially (United-Nation, 2020).…”
Section: Introductionmentioning
confidence: 99%